2012
DOI: 10.1098/rsbl.2012.0150
|View full text |Cite
|
Sign up to set email alerts
|

Low dose ionizing radiation produces too few reactive oxygen species to directly affect antioxidant concentrations in cells

Abstract: It has been hypothesized that radiation-induced oxidative stress is the mechanism for a wide range of negative impacts on biota living in radioactively contaminated areas around Chernobyl. The present study tests this hypothesis mechanistically, for the first time, by modelling the impacts of radiolysis products within the cell resulting from radiations (low linear energy transfer b and g), and dose rates appropriate to current contamination types and densities in the Chernobyl exclusion zone and at Fukushima.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 18 publications
(27 reference statements)
3
47
1
1
Order By: Relevance
“…The amount of oxidizing radicals from UV to which ancient microbes had to adapt is orders of magnitude greater than those produced by IR-induced radiolysis at doses likely to occur in the environment (Smith et al, 2012), so we hypothesize that a threshold for oxidative effects IR exists for microorganisms because they are pre-adapted to withstand the limited oxidizing effects of IR at environmentally relevant dose rates. This suggests that there are doses, including chronic low doses, which are unlikely to have adverse effects on at least some microbial populations.…”
Section: Implications For the Environmental Toxicology Of Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of oxidizing radicals from UV to which ancient microbes had to adapt is orders of magnitude greater than those produced by IR-induced radiolysis at doses likely to occur in the environment (Smith et al, 2012), so we hypothesize that a threshold for oxidative effects IR exists for microorganisms because they are pre-adapted to withstand the limited oxidizing effects of IR at environmentally relevant dose rates. This suggests that there are doses, including chronic low doses, which are unlikely to have adverse effects on at least some microbial populations.…”
Section: Implications For the Environmental Toxicology Of Microorganismsmentioning
confidence: 99%
“…At low chronic doses of IR, such as those that occur in radioactively contaminated environments, there is currently a particular lack of toxicological consensus about the effects of IR on organisms. On the one hand, mechanistic calculations show that direct oxidative stress is not likely to be caused by chronic low doses of radiation (Smith et al, 2012) whilst some field studies suggest chronic low doses of IR affect the fitness of, for example, small mammals (Lehmann et al, 2016). It has even been suggested that variation in naturally-occurring levels of radioactivity can affect immune function, mutation, and disease in animals and plants (Møller and Mousseau, 2013).…”
Section: Dna Damage and Oxidative Stress In Microbes During Exposure mentioning
confidence: 99%
“…4). Это может быть связано с тем, что наблюдаемые мощности дозы недостаточны для ин-дукции физиологически значимого увеличения концен-трации активных форм кислорода в клетках сосны [32]. Этот вывод подтверждается тем, что активность анти-оксидантных ферментов в семенах сосны обыкновен-ной с ростом уровня радиоактивного загрязнения также не изменялась [15].…”
Section: активность ферментовunclassified
“…We strongly believe that cells have an internal oxidant/anti-oxidant rheostat, that, if tilted towards excessive ROS upon -let’s say- a radiation insult, then our anti-oxidant defense under the control of Kelch-like ECH-associated protein 1 (Keap1) / NF-E2-related factor 2/ (Nrf-2) and Heat shock factor (HSF-1) / Heat shock proteins (HSPs) kick in to correct that by driving an anti-oxidant/anti-inflammatory response (Figure 1)[64]. However, if the initial radiation dose is small, the ROS/DAMP levels may not rise above a certain threshold, and fail to activate the compensatory anti-oxidant response [34, 35, 65]. However additional PAMPs, e.g.…”
Section: First Come First Servedmentioning
confidence: 99%